2021
DOI: 10.3390/v13081623
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals the Potential Role of Long Noncoding RNAs in Regulating Fowl Adenovirus Serotype 4-Induced Apoptosis in Leghorn Male Hepatocellular Cells

Abstract: Hepatitis-hydropericardium syndrome (HHS) is caused by fowl adenovirus serotype 4 (FAdV-4) and has resulted in considerable economic losses to the poultry industry globally. FAdV-4 elicits apoptosis in host cells. Long noncoding RNAs (lncRNAs) have emerged as important regulatory RNAs with profound effects on various biological processes, including apoptosis. However, it remains unknown whether lncRNAs participate in FAdV-4-induced apoptosis. In this study, RNA sequencing was applied to determine the transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Cells were cultured for ~24 h to reach 80% confluence and subsequently infected with FAdV-4 (MOI = 0.1); uninfected LMH cells were used as a mock control. FAdV-4 infected with LMH Cells caused cytopathic effect (CPE), viral titers and viral loads as previously described ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured for ~24 h to reach 80% confluence and subsequently infected with FAdV-4 (MOI = 0.1); uninfected LMH cells were used as a mock control. FAdV-4 infected with LMH Cells caused cytopathic effect (CPE), viral titers and viral loads as previously described ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that viral infection alters the lncRNA transcription profile of infected host cells, which is involved in the establishment and maintenance of persistent infection ( Meng et al., 2017 ). It has been reported that FAdV-4 induces apoptosis in LMH cells by modulating the transcription of the BMP4 gene, which is targeted by lncRNA 54128 ( Wen et al., 2021 ). The miRNAs and lncRNAs whose transcription is induced during FAdV-4 infection, as well as their target mRNAs, are listed in Table 1 .…”
Section: The Potential Regulatory Effect Of Fadv-4 Infection On Ncrnasmentioning
confidence: 99%
“…The expression of SUMO-1 activating enzyme subunit ( SAE1 ) was greatly upregulated to restrict FAdV-4 infection in LMH cells ( Hou et al, 2021 ). Additionally, FAdV-4 elicited different expressions of long noncoding RNA ( lncRNA ), microRNA, and mRNA ( Wu et al, 2020 ) in infected LMH cells and lncRNA 54128 was identified to greatly suppress the virus induced apoptosis ( Wen et al, 2021 ). All these results suggested that viral and host factors jointly contributed to the pathogenesis of hypervirulent FAdV-4 strains.…”
Section: Introductionmentioning
confidence: 99%